Renovating Confucian ideas for gender equality: an inquiry of Confucian feminist debates in modern China - Wei Li (Humanities & Social Sciences Communications)
Abstract Contrary to the common perception that Confucianism is incompatible with feminist movement, this article demonstrates that Chinese intellectuals in the 1890s–1920s positively reconstructed and applied Confucian ideas that provide a theoretical and political path to gender equality. Deploying the immanent critique method and grounded theory method to analyze the texts and practices of the intellectuals, the study identified three anchoring elements of the Confucian feminism: 1. benevolent reciprocal and hierarchical relations that extend humanity to all and embrace contribution by all (expansive ren 仁); 2. critical (jian) dao, the way or path of applying ren, yi (义) and shu (恕) to the treatment of women (especially the less advantaged among them); 3. enabling and encouraging women’s cultivation for self-progression and contribution to a healthy society (xiuji da datong 修己达大同). Different from feminist political liberalism, Confucian feminism during the 1890s–1920s of China promoted the positive (e.g., benevolent and affective) features of reciprocal and hierarchical relations that enable women’s self-progression and societal contribution. It has potential to encourage transnational and global feminist politics that advance decolonial solutions from local social and cultural (particularly Asian) contexts.